The Influence of Perceived Convenience and Use of E-Banking on Utilization of Syari'ah E-Banking Services - Masruchin; Hayatudin, Amrullah; Ali Sayed, Fadwa; Wicaksono, Arief (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
The rapid development of technology encourages banking services to provide e-banking services. This study aims to investigate the influence of perceived ease and use of e-banking on the utilization of Islamic e-banking. The utilization of Islamic e-banking services among students has not been widely studied, so it is important to understand the factors that influenced it. The study used a quantitative approach with a survey method on 210 UMSIDA and UNISBA students who actively use Islamic e-banking. Data were collected through questionnaires and analyzed using SPSS version 22 analysis. The results showed that the perceived convenience and use of e-banking had a significant effect on the utilization of Islamic e-banking services. These findings can assist Islamic banking institutions in developing more effective strategies to attract and retain students as users of their services. This research also provides a scientific contribution in the field of Islamic banking and marketing studies, and can be a reference for future research on the utilization of Islamic e-banking services among university students. This research also indicates that the perceived ease and use of E-Banking are crucial factors in increasing the utilisation of Islamic E-Banking services.